1987
DOI: 10.1017/s000335610003659x
|View full text |Cite
|
Sign up to set email alerts
|

In vitrogas and foam production by rumen fluid from cows of genetically high or low susceptibility to pasture bloat

Abstract: Rumen fluid was obtained from rumen fistulated cows (two of high (HS) and two of low (LS) susceptibility to bloat) which were bred in experimental herds subjected to long-term divergent genetic selection for pasture bloat susceptibility. In vitro fermentation using strained rumen fluid from each cow with various pasture juice substrates showed no differences between HS and LS in gas production per unit of rumen fluid or in foam production per unit of gas production. Fluid from cows on grazed pasture produced g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Mangan and Johns (1957) investigated the foaming properties of white clover and found that the digitonin equivalents (related to foam persistence) of non bloat-inducing clover was only 21% less than from bloat-inducing clover. Cockrem et al (1987) also found that there was a lesser amount of foam produced from crude extracts of pastures on non-bloat days than on bloat days (P < 0.07) and the liquid to foam ratio (a measure of compressive strength) on non-bloat days was only 16 % less than on bloat days (P < 0.09). The use of monensin in a controlled release rumen capsule has been found to lower the incidence of pasture bloat in the dairy industry by 80% (Cameron and Malmo 1993).…”
Section: Effect Of Pa Concentration On Foam Properties and Bloatmentioning
confidence: 85%
See 1 more Smart Citation
“…Mangan and Johns (1957) investigated the foaming properties of white clover and found that the digitonin equivalents (related to foam persistence) of non bloat-inducing clover was only 21% less than from bloat-inducing clover. Cockrem et al (1987) also found that there was a lesser amount of foam produced from crude extracts of pastures on non-bloat days than on bloat days (P < 0.07) and the liquid to foam ratio (a measure of compressive strength) on non-bloat days was only 16 % less than on bloat days (P < 0.09). The use of monensin in a controlled release rumen capsule has been found to lower the incidence of pasture bloat in the dairy industry by 80% (Cameron and Malmo 1993).…”
Section: Effect Of Pa Concentration On Foam Properties and Bloatmentioning
confidence: 85%
“…In these studies foams were prepared from plant extracts and either the stability (Pressey et al 1963), the volume of foam formed (Kendall 1964;Cooper et al 1966), or foam strength (Jones et al 1970) measured over time. Cockrem et al (1987) studied foam production when strained rumen fluids were mixed with forage extracts and artificial saliva in a manner designed to more closely mimic the conditions in the rumen. White clover extracts produced more foam per unit of gas evolved than ryegrass extract.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle bloat because alfalfa has a rapid initial rate of digestion, which can be associated with acute changes in rumen microbial populations. Large numbers of encapsulated lactic acid streptococci contribute to a buildup of froth, as populations of Streptococcus bovis rise and the viscosity of rumen fluid increases (Majak et al 1983;Cockrem et al 1987). Persistent high viscosity foams cover the cardiac sphincter of the rumen, which inhibits normal eructation by the animal.…”
Section: Herbage Intakementioning
confidence: 99%
“…As a result, gases accumulate in the rumen leading to acute frothy bloat. Conditions favoring the production of persistent high viscosity foams include: 1) a balance of surface active materials in favor of foaming; 2) an environment provided by digesta favoring foam persistence; 3) adequate but not excessive gas production; 4) rumen pH ≤ 5.5, and 5) the presence of salivary mucoprotein (specifically albumin) enhancing foam stability (Majak et al 1983;Cockrem et al 1987). Often, mortality of livestock on pasture is attributed to bloat, which may not in fact be the case.…”
Section: Herbage Intakementioning
confidence: 99%
“…A major disadvantage of grazing cattle on alfalfa is its poor protein utilization (Broderick 1995;Yu et al 2004) and its tendency to cause pasture bloat Wang et al 2006b). Pasture bloat arises from rumen fermentation gases, which become trapped in a stable protein foam that prevents normal eructation of gas via the oesophagus by the animal (Cockrem et al 1987;Tanner et al 1995). Characteristic bloat-free legume forages like sainfoin (Onobrychis viciifolia), sulla (Hedysarium coronarium), birdsfoot trefoil (Lotus corniculatus), and big trefoil (Lotus pedunculatus) contain condensed tannin (CT), flavonoid polymers, which are also known as proanthocyanidin (Aerts et al 1999;Majak et al 1995;McMahon et al 2000).…”
mentioning
confidence: 99%